2021
DOI: 10.3390/ijerph18168647
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Financial Hardship, Job Loss, and Mental Health Symptoms: Findings from a Cross-Sectional Study in a Rural Agrarian Community in India

Abstract: Several countries, including India, imposed mandatory social distancing, quarantine, and lockdowns to stop the spread of the SARS-CoV-2 virus. Although these measures were effective in curbing the spread of the virus, prolonged social distancing, quarantine, and the resultant economic disruption led to an increase in financial stress and mental health concerns. Prior studies established a link between the first lockdown and an increase in mental health issues. However, few studies investigated the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
4
28
0
Order By: Relevance
“…This is a particular concern given how COVID-19 induced economic hardship is having adverse effects on the psychological well-being of the population. [34][35][36][37] These findings should be considered in light of a number of limitations. First, while this study provides unique and important insights into keyworkers' experiences during the pandemic, the timing of the interviews may need to be considered when interpreting the findings.…”
Section: Discussionmentioning
confidence: 96%
“…This is a particular concern given how COVID-19 induced economic hardship is having adverse effects on the psychological well-being of the population. [34][35][36][37] These findings should be considered in light of a number of limitations. First, while this study provides unique and important insights into keyworkers' experiences during the pandemic, the timing of the interviews may need to be considered when interpreting the findings.…”
Section: Discussionmentioning
confidence: 96%
“…Second, association of mental status with treatment cancellation and accessible care may be new direction in the future. This is can be reflected by several studies which reported the association between COVID-19-related financial situation and mental health [ 87 , 88 ]. If replicating in future studies, it is recommended that research with a longitudinal design be undertaken irrespective of crisis settings.…”
Section: Discussionmentioning
confidence: 97%
“…Psychologically, entrepreneurs were unsatisfied. It has been observed that, During the lockdown, financial stress and mental health symptoms were at their peak [15]. They didn't get any assistance from the government.…”
Section: Issues Challenges and Problems Of Rural Entrepreneursmentioning
confidence: 99%